Prevalence and Antibacterial Susceptibility in Mastitis in Buffalo and Cattle in District Lahore-Pakistan - Mustafa, Y.S.; Awan, F.N.; Zaman, T.; Chaudhry, S.R.; Zoyfro, V. (Journal of Buffalo Science, 2012)
A total of 450 milk samples including both 272 buffalo and 178 cattle were randomly collected in and around District Lahore to study the incidence of mastitis and antibiotic sensitivity by performing Culture and Sensitivity test. The prevalence of mastitis in buffalo was found 20.98% while in cattle 24.71%. The prevalence of both Clinical and subclincal mastitis in buffalo were 40.35%, 59.64% and in cattle 61.26%, 30.63% respectively. The milk samples mixed with both mucus and blood in buffalo and cattle were 5.51% and 4.49% respectively. Quarters wise prevalence was 47.72%, 11.36%, 36.36% and 4.54% in the left fore, left hind, right fore and right hind quarters in cattle while In buffaloes, the prevalence was 0%, 68.96%, 11.49% and 19.54% in the left fore, left hind, right fore and right hind quarters respectively. The Ciprofloxacin antibiotic was found highly Sensitive in buffalo while Gentamicin in cattle.